Trends and risk factors of mortality analysis in patients with inflammatory bowel disease: a Taiwanese nationwide population-based study - Lin, Wei-Chen (J Transl Med, 2019)
BACKGROUND: Inflammatory bowel disease (IBD) was emerging as a worldwide epidemic disease, and the advanced therapy changed the clinical course and possibly the outcomes. Our previous study reported a higher mortality rate from (IBD) in Taiwan than in Western countries. We proposed to analyze the trend and risk factors of mortality in order to improve the care quality of IBD patients. METHODS: This retrospective study was conducted to analyze data for January 2001 to December 2015 from a registered database, compiled by the Taiwan’s National Health Insurance. RESULTS: Between 2001 and 2015, a total of 3806 IBD patients [Crohn’s disease (CD): 919; ulcerative colitis (UC): 2887] were registered as having catastrophic illness, and 8.2% of these patients died during follow-up. The standardized mortality ratios (SMRs) of CD and UC were 3.72 (95% CI 3.02–4.55) and 1.44 (95% CI 1.26–1.65), respectively, from 2001 to 2015, respectively. A comparison of the periods of 2011–2015 and 2001–2005 revealed a decrease in the mortality rates from both UC and CD. Multivariate Cox proportional hazards analysis identified elderly individuals; sepsis and pneumonia were the risk factors for IBD mortality. The specific risk factors of mortality were liver cancer for UC and surgeries for CD. CONCLUSION: For further decreasing IBD-related mortality in Taiwan, we need to pay special attention toward elderly individuals, infection control, cancer screening and improvement in perioperative care.